2007 7th IEEE Conference on Nanotechnology (IEEE NANO) 2007
DOI: 10.1109/nano.2007.4601196
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of Fe-Co nanoparticles, magnetotactic bacteria and Fe3O4 microparticles for future drug delivery applications

Abstract: -Magnetic resonance imaging characteristics of novel potential drug delivery agents are investigated. Candidate carriers considered in this study are iron-cobalt (Fe-Co) nanoparticles, magnetotactic bacteria (MTB), and magnetite (Fe 3 O 4 ) microparticles. The micro and nanoparticles are highly magnetic and can be steered using gradient coils. MTB, on the other hand, are microorganisms that naturally follow the magnetic field lines through a mechanism called magnetotaxis. These carriers share the capability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…MNPs isolated from bacterial cells have also been coated with biopolymers including chitosan, N-trimethylchitosan, carboxymethylchitosan and dextran to provide biocompatible surfaces for medical applications(466).MNPs are commonly used as contrast enhancers of magnetic resonance imaging (MRI) for medical and diagnostic purposes(467)(468)(469). MNPs from MTBs and the bacterial cells were shown to be easily controllable and detectable by MRI and they were proposed as potential enhancers for MRI imaging and carriers of treatment medications for targeted delivery(418,470). Later it was reported that viable MTBs cells can be directly used as MRI contrast enhancers(420,(471)(472)(473).…”
mentioning
confidence: 99%
“…MNPs isolated from bacterial cells have also been coated with biopolymers including chitosan, N-trimethylchitosan, carboxymethylchitosan and dextran to provide biocompatible surfaces for medical applications(466).MNPs are commonly used as contrast enhancers of magnetic resonance imaging (MRI) for medical and diagnostic purposes(467)(468)(469). MNPs from MTBs and the bacterial cells were shown to be easily controllable and detectable by MRI and they were proposed as potential enhancers for MRI imaging and carriers of treatment medications for targeted delivery(418,470). Later it was reported that viable MTBs cells can be directly used as MRI contrast enhancers(420,(471)(472)(473).…”
mentioning
confidence: 99%